2021
DOI: 10.3390/agronomy11050863
|View full text |Cite
|
Sign up to set email alerts
|

Maximizing Land Use Efficiency and Productivity of Soybean and Fodder Maize Intercrops through Manipulating Sowing Schedule and Maize Harvest Regime

Abstract: The incorporation of both food and forage crops in an intercropping system is receiving increasing attention, especially in developing countries with increasing populations and limited resources. In a two-year (2019–2020) field trial, conducted in Northern Egypt, productivity of soybean and fodder maize, as well as the quality of maize herbage, were investigated under three sowing schedules; soybean and maize sown together, and maize sown 15 and 30 days after soybean, in addition to soybean and fodder maize so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…In the intercropping practice, competition among the component crops, mainly for light, soil water and nutrients, is among the crucial factors that determines the variations in their productivity [35]. Several previous studies reported lower yields for cereal-legume intercrops compared to sole crops [4,9,24]. They attributed this to the interspecific competition between the different component crops.…”
Section: Impact Of Intercropping Patternmentioning
confidence: 99%
See 2 more Smart Citations
“…In the intercropping practice, competition among the component crops, mainly for light, soil water and nutrients, is among the crucial factors that determines the variations in their productivity [35]. Several previous studies reported lower yields for cereal-legume intercrops compared to sole crops [4,9,24]. They attributed this to the interspecific competition between the different component crops.…”
Section: Impact Of Intercropping Patternmentioning
confidence: 99%
“…Recently, intercropping has been considered an effective strategy to enhance the resilience of the farming system to climate change hazards [1]. Cereal-legume intercropping is a widely proposed strategy to develop a sustainable food and forage production system [2,3] to replenish the food and feed gaps, especially in developing countries with restricted agricultural inputs [4,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The superiority of plant height of forage crops associated with dense sowing of maize plants may be explained by high inter specific competition between plants on light which caused an elongation in the internode length. In this concern, many researchers found that the intercropping increased the plant height of millet when intercropped with cowpea (Mohamed et al, 2020) and sorghum when intercropped with cowpea (Chaudhary et al, 2020) as well as fodder maize when intercropped with soybean (Salama and Abdel-Moneim, 2021). Moreover, Omoregie et al (2020) noticed that plant height of millet was increased by increasing the competition among plants especially at the highest plant density of millet.…”
Section: -Effect Of Intercropping Of Forage Crops 1-1 Growth Charactersmentioning
confidence: 99%
“…These results are in harmony with those obtained by Hassan et al (2017) who found that pearl millet gave the highest values of fresh and dry yields/fed followed by sudan grass and teosinte when they were grown either alone or intercropped with some legume crops. Also, many investigators found that fresh and dry forage yields/unit area of some grass forage crops were decreased when they were intercropped with some crops such as maize (Samarappuli and Berti, 2018), cowpea (Shahwan et al, 2013, Pal et al, 2014, Iqbal et al, 2017, Ginwal et al 2019and Qadir et al, 2021 and soybean (Salama andAbdel-Moneim, 2021 andSoe Htet et al, 2021).…”
Section: -2 Forage Productionmentioning
confidence: 99%